Occupational Safety and Health as a Fundamental Human Right - Indacochea Jauregui, Juan Manuel; Huancahuari Moya, Javier (Revista Tribuna Internacional, 2021)
Although the first regulations on workplace safety and health emerged in the 19th century, this area of Labor Law has continued to develop according to the political commitment of each country. The scope of protection of occupational safety and health has been extended with the ratification of the Conventions of the International Labor Organization (ILO), as well as the compliance with the International Covenant on Economic, Social and Cultural Rights (ICESCR) and the Additional Protocol to the American Convention on Human Rights in the Area of Economic, Social and Cultural Rights (Protocol of San Salvador). The purpose of this paper is to analyze the international treaties and the regional legal framework related to the international protection of the human right to safe and healthy work, while explaining the relevant regional jurisprudence, in order to define the minimal content of this fundamental human right.